Utilization of Infrastructure a in Improving Guidance and Counseling in Schools - Desi Harlina; Riska Ahmad; Yarmis Syukur (Universitas PGRI SUMATERA BARAT, 2023)
This article discusses the use of infrastructure as a support for improving counseling activities in schools. The utilization of school infrastructure, especially guidance and counseling, is often not given proper attention. So that the implementation of guidance and counseling is difficult to run optimally. For this reason, it is necessary to utilize guidance and counseling infrastructure to encourage the implementation of guidance and counseling so that they can run effectively. The purpose of writing this article is to find out how infrastructure can improve guidance and counseling services in schools. The method used in writing this article is a literature study. The results of the discussion in this article are that the utilization of infrastructure can be carried out by paying attention to standards related to infrastructure that must be completed in the guidance and counseling room and forming strategies in infrastructure management.